2018
DOI: 10.3390/en11020327
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Trees and Their Growth in Silicone Rubber at Various Voltage Frequencies

Abstract: Abstract:The insulation property at high voltage frequencies has become a tough challenge with the rapid development of high-voltage and high-frequency power electronics. In this paper, the electrical treeing behavior of silicone rubber (SIR) is examined and determined at various voltage frequencies, ranging from 50 Hz to 130 kHz. The results show that the initiation voltage of electrical trees decreased by 27.9% monotonically, and they became denser when the voltage frequency increased. A bubble-shaped deteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, the maximum frequency studied for electrical treeing degradation in the literature only reaches 130 kHz [42] and this was for silicone rubber (a solid dielectric) and not for silicone gel. It was observed that electrical trees tend to be denser and larger with rising frequency; when the frequency exceeds 100 kHz, bubble breakdown occurs in a very short time, as shown in Figure 7.…”
Section: (B) Effect Of Voltage Waveform and Frequencymentioning
confidence: 92%
“…To the best of our knowledge, the maximum frequency studied for electrical treeing degradation in the literature only reaches 130 kHz [42] and this was for silicone rubber (a solid dielectric) and not for silicone gel. It was observed that electrical trees tend to be denser and larger with rising frequency; when the frequency exceeds 100 kHz, bubble breakdown occurs in a very short time, as shown in Figure 7.…”
Section: (B) Effect Of Voltage Waveform and Frequencymentioning
confidence: 92%
“…When the traditional tree generated from the bubble, its volume obviously decreased. It can be assumed that in the bubble stage, there is a lot of gas inside it [41] and the different probabilities of bubble tree can be explained by the inception mechanism shown in Figure 11. There may be some small cavities near the needle tip for two reasons: (1) the high Maxwell compressive force caused by the prestressing DC; or (2) different thermal expansion of SIR and needle tip [34].…”
Section: Effects Of Different Prestressing Timesmentioning
confidence: 99%
“…Partial discharge (PD) is a phenomenon which occurs when there is an electrical discharge within a localized area as stated in IEC 60270 [3]. These internal arcs promote the breakdown of insulation, forming electrical trees [4,5]. Once the electrical tree has threaded sufficiently deep, it will exposed the copper conductor to the environment, resulting in a cable failure and risk of current leakage to the tunnel platform [6].…”
mentioning
confidence: 99%